Eradication and Current Status of Poliomyelitis in Pakistan: Ground Realities. (18th July 2016) - Ghafoor, Shazia; Sheikh, Nadeem
Abstract : Pakistan is among the last three countries along with Afghanistan and Nigeria, where polio virus is still endemic. More or less, with some fluctuations, numbers of reported cases in the past few years have shown a rising trend. Year 2014 pushed the country into the deep sea of difficulties, as number of cases rose to red alert level of 328. Security situation has adversely affected the whole immunization coverage campaign. In a country where 40 polio vaccinators have been killed since 2012, such a big number of cases is not a surprising outcome. Worse perception of parents about polio vaccine as in Karachi and FATA, the high risk zones, makes 100% coverage a dream. Minor and perhaps delayed payments to polio workers make them frustrated, resulting in decline of trained manpower for vaccination. Strong implementation of policies is required and those found guilty of attack on polio workers need to be punished. Targeted community awareness programme, strong surveillance network, and involvement of influential religious entities can help to root out polio disease from country. Present review is aimed at analyzing all barriers on the road to success in eradication of polio from Pakistan.